Performance Evaluation of a Generator Differential Protection Function for a Numerical Relay - Le, K. H.; Vu, P. H. (Engineering, Technology & Applied Science Research, 2019)
This paper describes the advantages and disadvantages of a generator differential protection relay system which uses double slope characteristics of Areva P343, ABB REG670, SEL300G and GE G60. A Buon Tua Srah Hydropower Plant in Vietnam was selected as an example for the relay setting calculations of these characteristics. The performance of the introduced relay model was tested at various fault conditions in Matlab/Simulink. The results apply to the problems of solving the performance of the relay accurately and with reliable differential protection against internal faults, and keeping the generator stable on all external faults and in normal conditions. The simulation simplifies the process of selecting the relay and protection system. This can improve the quality of the protection system design early, thereby reducing the number of errors found later in the operation.